LDC export diversification, employment generation and the "green economy": What roles for tourism linkages? - Dale Honeck (World Trade Organization (WTO), 2012)
Pro-poor tourism is arguably one of the best green options for addressing LDC poverty, employment and economic diversification initiatives. Although often neglected as a serious policy option - and consequently most of its potential still remains untapped - tourism is the leading export for at least 11 LDCs, and the 2nd or 3rd largest export for another 11 or more. It is also a major source of new employment, especially for women, youth and the rural poor in general. While difficult to measure accurately, tourism's pro-poor impacts are directly related to the achieved level of inter- and intra-sectoral linkages. Taking export diversification, employment generation and the green economy in turn, the working paper analyzes feasible LDC alternatives, reaching the conclusion (within the limits of data availability) that - in contrast with the current overemphasis on agriculture and manufacturing - green tourism is demonstrably one of the areas of greatest current comparative advantage and development potential for the majority of LDCs, via its extensive upstream and downstream linkages/multiplier effects, employment-generating and poverty alleviation capacities, opportunities for export test marketing of new products, sustainability, and largely untapped export opportunities. An economy wide, primarily private-sector approach is an essential element for maximizing tourism benefits - including its multiple linkages with agriculture and manufacturing - together with a significant coordinating governmental role to minimize negative externalities. Unfortunately, there is no automatic guarantee that expanding tourism will significantly increase poverty alleviation or local employment generation: the necessary mechanisms must be explicitly included in tourism planning and implementation.
Keywords: F13; F18; H54; H77; I38; J16; J21; J24; K39; L52; L83; O14; O19; O24; P45; Q26; Q54; Q56; 330; LDCs; LDC Graduation; Export Diversification; Development; Comparative Advantage; Employment Generation; Green Economy; Green Tourism; Pro-poor Tourism; Tourism Linkages; Cluster Analysis; Value Chain Analysis; Poverty Alleviation; MDGs; Gender Issues; FDI; GATS; Africa; Istanbul Programme of Action (IPoA); Rio+20; Armut; Beschäftigung; Exportdiversifizierung; Nachhaltige Entwicklung; Tourismuspolitik; Entwicklungsländer